Exploring the Potential of Sumedang Walkers as a Community-Based Sport Tourism Destination - Nurhaliza, Alya Sri; Fauzi, Rizal Ahmad; Sudrazat, Adang (Journal Coaching Education Sports, 2026)
This study explores the potential of Sumedang Walkers as a community-based sport tourism destination in Sumedang Regency, Indonesia. A qualitative phenomenological approach was employed to understand the experiences and perceptions of community members and stakeholders involved in the development of sport tourism activities. Data were collected through observations, in-depth interviews, and documentation involving community organizers, participants, local residents, MSME actors, and representatives of the Tourism Office. The study applied the MSPDM framework consisting of marketability, sustainability, participation, and disaster mitigation. Data analysis was conducted using thematic coding supported by NVivo 12 through data reduction, categorization, triangulation, and interpretation. The findings indicate that Sumedang Walkers possesses strong tourism potential supported by natural attractions, unique walking routes, community participation, and local economic involvement. In addition, disaster mitigation awareness and environmental sustainability practices contribute to the safety and continuity of tourism activities. This study proposes an Integrated Community Sport Tourism Sustainability Framework that integrates tourism attractiveness, environmental sustainability, participatory governance, and disaster preparedness in developing sustainable community-based sport tourism.